2020
DOI: 10.18502/jad.v14i2.3738
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of Scorpionism in West Azerbaijan Province, Northwest of Iran

Abstract: Background: There are four medically important scorpion species (Mesobuthus eupeus, Mesobuthus caucasicus, Androctonus crassicauda and Hottentotta saulcyi) in the West Azerbaijan Province, northwestern Iran. scorpionism is considered as a health problem in this region, because there is no information about scorpion envenomation, this study was designed to study epidemiological characteristics of scorpionism to optimize prevention and treatment of scorpion sting in northwest of Iran. Methods: All the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…13 Several studies in Brazil and in other countries have reported seasonality in the occurrence of scorpion stings. [14][15][16][17][18] Accidents by scorpions show a constant variation, tending to be more frequent in the hottest and rainy seasons. This behavior of accentuated seasonal variation is well observed in the South, Midwest and Southeast regions, but is less pronounced in the Northeast and North regions, which may reflect the less evident seasons in these areas.…”
Section: Resultsmentioning
confidence: 99%
“…13 Several studies in Brazil and in other countries have reported seasonality in the occurrence of scorpion stings. [14][15][16][17][18] Accidents by scorpions show a constant variation, tending to be more frequent in the hottest and rainy seasons. This behavior of accentuated seasonal variation is well observed in the South, Midwest and Southeast regions, but is less pronounced in the Northeast and North regions, which may reflect the less evident seasons in these areas.…”
Section: Resultsmentioning
confidence: 99%
“…Por ser uma região tropical, as quatro estações do ano não estão bem definidas, mas a Primavera marca a chegada de temperaturas elevadas e a precipitação torna-se mais intensa e também mais frequente. Resultados semelhantes foram encontrados noutras áreas brasileiras [96,120] ) em outros países [48,[121][122][123] , onde o escorpionismo têm sido mais frequentes nos períodos mais quentes e chuvosos do ano. Por outro lado, outro estudo [100] mostrou uma uniformidade de ocorrência de escorpiões durante os meses do ano, o que poderia ser explicado pelas temperaturas ideais, umidade e alimentos abundantes ao longo do ano.…”
Section: Needleman Et Al (2018)unclassified